Optimization design of large span portal-rigid steel frame with tapered sections under wind-induced drift constraint. (1st September 2019) - Fu, J.Y.; Wu, J.R.; Dong, C.C.; Xu, A.; Pi, Y.-L.
Highlights: An Optimality Criteria method was proposed for the wind resistant structural optimization of a portal steel frame. The GLF based, single objective LRC-based and multiple objective universal-based ESWLs were derived for the large-span portal frame. The effect of different forms of ESWLs, the stiffness of support restraint and semi-rigid connection on the optimized results were analyzed. The optimized section heights of rafters and columns for minimum structural weight were obtained under wind-induced drift constraint. Abstract: Large span portal-rigid frames with tapered sections in low-rise metal building system are often used in industrial and commercial buildings. The drift of such portal-rigid frames induced by the wind load needs to be smaller than a prescribed limit, and at the same time the frames should be as light as possible for cost-effectiveness. To this end, structural optimization of such portal-rigid frames subjected to the wind-induced drift constraint is required. However, little research for optimization of the large span portal-rigid frame with tapered sections has been reported. This paper proposed a procedure for structural optimization of such portal-rigid frames by adopting the Optimality Criteria (OC) method. Based on an aerodynamic database of the measured wind pressure from a wind tunnel test, several forms of the Equivalent Static Wind Load (ESWL) acting on a large-span portal-rigid frame were evaluated by the Gust Loading Factor (GLF), Load Response Correlation (LRC) and Proper Orthogonal Decomposition (POD) method. The method of virtual-work was utilized to construct the wind-induced drift or displacement. An effective iteration algorithm was derived for the minimum weight optimization of the frame while all wind-induced drift constraints were satisfied. The wind resistant structural optimization for the large-span rigid frame with taped section were conducted when it was bore by different forms of ESWL (GLF based, single objective and multiple objective ESWLs), and their optimized results were multi-compared in the form of the optimized total weight and the height of the optimized structural members. The effects of the connection stiffness at semi-rigid joints and the stiffness of support restraints on the optimized results are also investigated. Finally the global optimality property of the proposed OC method adopted for the optimized case in this paper was also discussed and verified. Optimized results show that the OC optimization procedure proposed in this paper is very effective for the optimization design of large-span portal-rigid steel frames with tapered sections under wind-induced drift constraints.